Estimation of heritability and breeding values for performance and body conformation traits in Harnali Sheep - KUMAR, SANDEEP; DAHIYA, SATPAL; MAGOTRA, ANKIT; RATWAN, POONAM; BANGAR, YOGESH C (The Indian Journal of Animal Sciences, 2022)
The present study was conducted to evaluate the effect of non-genetic factors on performance and body conformation traits along with estimation of heritability and breeding values of these traits in Harnali sheep. Nongenetic factors had significant effect on the performance and body conformation traits in Harnali sheep. Heritability estimates varied from low to moderate for performance traits indicating the presence of genetic variability which could be used for further improvement of these traits. Comparatively higher heritability estimates for body conformation traits in the present study indicated towards the presence of genetic variability which might be due to the reason that linear type traits were not included in the selection criterion of Harnali sheep so far. High genetic variability in these traits noticeably indicated the scope of improvement in these body dimensions through selection. Breeding value estimates for different performance and body conformation traits pointed the variability between the genetic merit of individuals which can be exploited through selection for making improvement in the considered traits in Harnali sheep.